THE INFLUENCE OF USING VAK (VISUAL, AUDITORY, KINESTHETIC) LEARNING MODEL ON THE STUDENTS’ ACHIEVEMENT IN WRITING SHORT STORY TEXT AT SECOND GRADE SMP IT AL-HIJRAH 2 DELI SERDANG - Tien Rafida (UIN Sumatera Utara, 2018)
This research deals with the application of VAK (Visual, Auditory, Kinesthetic) learning model on students achievement in writing short story text. It was conducted by using experimental research. The aim of the research was to find out whether the use of VAK learning model has a significant influence on the the students’ achievement in writing short story text. This research was conducted to at class VIII SMP IT Al Hijrah 2 Deli Serdang 2015/2016. The subject of this research was the class VIIIA and VIIIB. They were 55 students. The research data were taken from the subject and the English teacher. This research was quantitative research. The population of this research was all students’ class VIII SMP IT Al Hijrah 2 Deli Serdang was 55 students. The sample of this research taken from 21 students’ experiment class and 34 students’ control class. The instrument for collecting data was a test. The data was analyzed by using t-test formula with the data showed that mean experiment class was 74 and control class was 60.94. The variant of using VAK learning model was 100.1 and the variant of without using VAK learning model was 174.54. The result of the analysis showed that tcount = 4.49 was higher than t table = 2.001 with the level significant 0,05. From the result, the researcher found that there was significant influence of the students’ achievement in writing short story text were taught by using VAK (Visual, Auditory, Kinesthetic) learning model. It meant alternative hypothesis (Ha) was accepted and null hyphothesis (Ho) was rejected.Keyword: VAK Learning Model, Short Story Text, Students’ Achievement in Writing